Gender Bias and Sexual Harassment in the Mining Industry: Unceasing Hurdles to Females’ Career Development and Work Safety - Sarah Karen Iradukunda; Obed Nahayo; Pinky Saptandari (Universitas Airlangga, 2021)
Introduction: Gender issue has been tremendously discussed all over the world, and it inhibits females’ career development and work safety. Nevertheless, it specifically persists in the mining industry and continues to discourage women from developing and managing their careers in the mining industry. Moreover, gender issue hampers their work safety as well in spite of the fact that researchers have estimated that around 10% of females work in the mining sector. This research aims to explain how gender bias and sexual harassment in the mining industry hamper females’ career development and work safety, which in turn affects this industry’s sustainable development. Methods: The method of this study was qualitative descriptive research approach, and the snowball sampling technique was used, where researchers selected 23 informants who had experienced gender bias and sexual harassment while working in mining companies. Phone interviews were conducted, and informants answered questions about gender bias and sexual harassment in the workplace towards their career development. Transcription, segmentation and conceptualization were done to analyze data. Results: The research results have shown that gender bias and sexual harassment are big stumbling blocks not only to women’s career development and work safety in the mining sector but also to the industry itself. The research has revealed that the hiring process, where most women get rejected because of wrong perceptions and cultural background that mining-related works are for men, plays a big role in this issue. Moreover, those who are hired are not taken care of. Conclusion: Gender bias and sexual harassment significantly affect career development of female workers, and they also hinder their work safety and financial stability.Keywords: career development, mining, gender bias, sexual harassment, work safety